Doctorate in Scientific Research with a mention in Health Sciences, period 2021-2025: Achievements and Advances (Revista Torreón Universitario, 2023)
With the aim of publicizing the achievements and advances of the Doctoral Program in Scientific Research with a mention in Health Sciences, (PRODIC_S), I Cohort of the Faculty of Medical Sciences (FCCMédicas) of UNAN-Managua, this article is presented. The following stand out as relevant findings: 1) Defended the Doctoral Research Project of each doctoral student. (2) Compliance with the academic plan for the year 2021. (3) Defined the Scientific Tutor for each of the doctoral students. (4) As of June 30, 2022, 80% of doctoral students are awarded scholarships by UNAN-Managua. (5) High satisfaction was obtained from the doctoral students regarding their progress in the program, 90% had very high satisfaction and 10% had high satisfaction. (6) Access and availability to academic material, through the Moodle Platform of the doctorate. (7) Compliance with the first scientific test. (8) Institutional management of the program based on the I+D+i Model. (9) Completion of the doctoral research project. (10) Developed a new curricular design in six modules. (11) Availability of the Founding Teachers Team of this program.
Keywords: Achievements and progress; Doctorate in Scientific Research